Robotising vitreoretinal surgeries - Mi, H; MacLaren, RE; Cehajic-Kapetanovic, J (Nature Publishing Group UK, 2024)
The use of robotic surgery in ophthalmology has been shown to offer many potential advantages to current surgical techniques. Vitreoretinal surgery requires complex manoeuvres and high precision, and this is an area that exceeds manual human dexterity in certain surgical situations. With the advent of advanced therapeutics such as subretinal gene therapy, precise delivery and minimising trauma is imperative to optimize outcomes. There are multiple robotic systems in place for ophthalmology in pre-clinical and clinical use, and the Preceyes Robotic Surgical System (Preceyes BV) has also gained the CE mark and is commercially available for use. Recent in-vivo and in-human surgeries have been performed successfully with robotics systems. This includes membrane peeling, subretinal injections of therapeutics, and retinal vein cannulation. There is huge potential to integrate robotic surgery into mainstream clinical practice. In this review, we summarize the existing systems, and clinical implementation so far, and highlight the future clinical applications for robotic surgery in vitreo-retina.